Factors associated with functional health literacy and the quality of life of riverside residents served by the primary care network in the Brazilian amazon: a cross-sectional study - Ana Kedma Correa Pinheiro; Carlos Eduardo Raymundo; Eliene do Socorro da Silva Santos; Marcio Yrochy Saldanha dos Santos; Adriana de Oliveira Sarefino; Maria Helena do Nascimento Souza; Ingrid Bentes Lima; Raquel Gomes da Silva; Laura Maria Vidal Nogueira (BMC Primary Care)
Abstract Background the riverside population lives in a vulnerable social situation, shaped by geographical, economic, social, and educational aspects that have repercussions on health literacy, the limitations of which can compromise Quality of Life. These specificities influence the actions of Primary Health Care, especially in the rural context. This study aimed to assess the factors associated with Functional Health Literacy and Quality of Life among riverside residents of the Brazilian Amazon who use Primary Health Care. Methods a cross-sectional study with 312 users of a riverside Family Health Team, using the Health Literacy Test, classified as adequate, limited, and inadequate, and the Study Short Form 12 Health Survey questionnaire, analyzing the physical and mental components in isolation. A theoretical model was built to assess the associations between sociodemographic and environmental variables and the Functional Health Literacy and Quality of Life outcomes. The Functional Health Literacy outcome was considered as two dichotomous variables (inadequate versus adequate; limited versus adequate), while the Quality of Life outcomes were considered as counts, with a Poisson distribution. Thus, a structural equation model was used to adjust the proposed theoretical model. Results there was a worsening in inadequate Functional Health Literacy, associated with females, aged over 40, elementary school education, living close to the health service, and using only a cell phone for communication. Factors that compromised physical Quality of Life: livelihood problems; inadequate literacy; age range 40–59; and having two children or more. And those that worsened mental Quality of Life: age over 40; having a family allowance; and being in control of their medication. Conclusions sociodemographic, environmental, and economic factors and adherence to medication by river communities have been shown to be associated with Health Literacy and Quality of Life. Knowing these implications is fundamental for health provision. These findings can support the formulation of strategies in health services to improve Health Literacy and Quality of Life.